2006
DOI: 10.1097/01.ccm.0000218810.66485.01
|View full text |Cite
|
Sign up to set email alerts
|

Hypertonic saline enhances host defense to bacterial challenge by augmenting Toll-like receptors*

Abstract: Restoration of extracellular fluid in burn shock with hypertonic saline decreased thermal injury-induced bacterial translocation. Hypertonic saline increased the phagocytic activity and TLR2, TLR4, CXCR2, pp38, and P44/42 expression of peritoneal cells. Hypertonic saline decreased reactive oxygen species but increased TLR2, TLR4, and pp38 expression and phagocytic activity of bone marrow neutrophil. Stimulation of the TLRs with lipopolysaccharide in commensal depleted mice increased TLRs expression of neutroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…Chen et al [25] showed that hypertonic resuscitation in a burned mouse model decreased bacterial translocation by increasing phagocytic activity of peritoneal and systemic inflammatory cells. This report may not yet be applicable at the bedside, but it should serve to remind clinicians that the effects of our interventions are not all apparent on rounds or in the clinical laboratory.…”
Section: Infectionmentioning
confidence: 99%
“…Chen et al [25] showed that hypertonic resuscitation in a burned mouse model decreased bacterial translocation by increasing phagocytic activity of peritoneal and systemic inflammatory cells. This report may not yet be applicable at the bedside, but it should serve to remind clinicians that the effects of our interventions are not all apparent on rounds or in the clinical laboratory.…”
Section: Infectionmentioning
confidence: 99%
“…Chen et al [114] evaluated the effects of HS on the thermal injury in mice with a particular emphasis on in vitro and in vivo host defense to bacterial challenge. This study reported that HS treatment decreased bacterial translocation, enhanced phagocytosis and clearance of bacteria as well as increased the expressions of TLR2, TLR4, CXCR2, pp38, and p44/42 in the peritoneal cells and neutrophils.…”
Section: Molecular and Cellular Effects Of Hsmentioning
confidence: 99%
“…Recently it has been shown in a mouse model post thermal injury that hypertonic saline enhances host defense to bacterial challenge by augmenting TLRs [156] . Nebulised hypertonic saline, although a different mode of delivery and for a different purpose, may in fact work in a similar way.…”
Section: Mucolytic Therapiesmentioning
confidence: 99%